Experiences with a structured conversation tool: a qualitative study on feasibility in general practice in Norway - Cathrine Abrahamsen; Morten Lindbaek; Erik L. Werner (Taylor & Francis Group, 2022)
AbstractObjective To study the feasibility of a structured conversation tool (ICIT) in Norwegian general practice.Design and participants A structured conversation tool with elements from Cognitive Behavioral Therapy (CBT) was developed for use at the encounter in general practice to increase patient's self-coping ability and the GPs management and sick leave assessment in patients with MUPS. Eight GPs received training and used the ICIT on 49 patients with MUPS. The physicians were gathered into two focus groups. The interviews were recorded on tape, transcribed, and analyzed with systematic text condensation.Main outcome measures The aim of our study was to examine any benefit and the feasibility of the ICIT in general practice.Results The physicians found the ICIT helpful to sort out, clarify and concretize the patients' issues. They felt less fatigued as patients took on a greater responsibility for their own recovery and reported a greater satisfaction and better management with the patients. A salutogenic approach gave the physicians greater insight into their patients' lives and their issues, opening for new treatment options and aiding in recovery. By focusing on the patient's potential capabilities despite their medical condition, some physicians experienced that patients on sick leave returned to work quicker.Conclusions The GPs in this study reported that the ICIT was helpful in consultations with patients due to unspecific medical conditions and facilitated a sense of competence for the physician. KEY POINTSGPs need communication skill training for integrated treatment and sick leave assessment for patients with Medically Unexplained Physical Symptoms (MUPS).•The GPs experienced that the structured conversation tool was beneficial in structuring, clarifying, and substantiating the patient's problems.•The GPs experienced a greater insight into their patients and their issues, opening new treatment options and aiding in recovery.•The GPs experienced patients' quicker recovery and returns to work by starting immediate treatment using the conversation tool.